Marta Suplicy, cenogragia e ethos político nos debates pela TV - Marchi, Alexandre (2010)
The politics was always a wide and fertile field for the teatralidade. We believed that the politicians, in general, look for to have ability to build an image of itself, a valued discursive ethos and that it is inspiring of trust, waiting that, like this, it can produce an identification with the voter, with consequent return in the in the election. With base in Dominique Maingueneau's studies (2005), we analyzed in that work mainly the interdiscurso concepts, of set design and of ethos taking as investigation object the political campaign of candidate to the city hall of São Paulo in 2008, Marta Suplicy. It is known that the ethos that is transmitted to the word, to the manifestation of the subject of the enunciation and that the power of persuasion of a speech consists partly of taking the reader identifying with the movement of a body invested of values socially specified. We understood that in spite of the word and the image they belong to specific partner-discursive universes, it is undeniable that in the speeches midiáticos his/her relationship is of reverse interdependence. In that way, we took as main object of analysis two debates of the second shift of the elections 2008 for the majority position of the city of São Paulo accomplished among candidates to the position, Gilberto Kassab, of Partido Democratas DEM, and Marta Suplicy, of Partido dos trabalhadores PT, in that confront their political accomplishments. We looked for to investigate as in that set design candidate and politics of long date Marta Suplicy, it institutes a discursive ethos that also she let to glimpse in the colors used in his/her clothing, in the accessories, in the tone and care with the choice of the words. Besides, we wanted to investigate if there are removal or adherence to his/her pré-discursive ethos, built and given to know openly in the end of the decade of 1970 and beginning of the decade of 1980, in the program TV MULHER, daily exhibited by the NET television GLOBE; in other words, as it is confronted in that debate a pré-discursive ethos that frequents imaginary national and a discursive ethos that candidate spreads of itself in that electoral campaign.